Promoting Lampung’s coffee to the Small Medium Enterprises (SMEs) in Turkey - Rindu Rika Gamayuni; N. Nairobi; Ernie Hendrawaty; Agrianti Komalasari; Arif Darmawan (Journal of Community Service and Empowerment, 2024)
Coffee producers in Indonesia need help with product quality, capital, and marketing. This international Community Service activity aims to promote Lampung coffee to the Turkish coffee market and improve the quality of Lampung coffee production and marketing. The activities were carried out in Istanbul, Turkey, with participants consisting of lecturers and students of the Master of Accounting FEB University of Lampung and management/employees of Kahvegihbikahve, one of the SME's coffee producers in Istanbul, Turkey. The activity was carried out through three main stages: (1) Preparation: situation analysis, preparation of material, making brochures for Lampung coffee producers; (2) Implementation: providing material to participants discussion to strengthen understanding and application of the material. (3) Evaluation and Reporting: comprehensive evaluation of community service results so that the participants can get to know the characteristics and taste of coffee in two countries (Indonesia, especially Lampung coffee and Turkish coffee), can understand and learn strategies for increasing the quality and quantity of coffee products and their marketing. So, it can make a positive contribution to the Indonesian and Turkish economies by increasing exports of coffee products and expanding the introduction of Indonesian coffee culture and taste.